(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
This article makes a reconstruction of the history of the International Day of the Roma as a symbol-date of the emergence of a transnational Roma political identity as a result of the globalization process initiated after the post-war period by the action of supranational organizations. I will also analyze the social dynamics resulting from this commemorative date from my ethnographic notes collected in the city of Valladolid during the rituals held in 2015 and 2016. In particular, I will investigate the roles of the State and other mediators imbued with a humanitarian ideology, together with the situated appropriations of the Romani themselves participating in this event that claims to be the most important of the international Roma community Palabras clave: Gitanos, Valladolid, Recognition policies, inequality, International Romani Day